IRE1/XBP1 and endoplasmic reticulum signaling — from basic to translational research for cardiovascular disease. Issue 28 (August 2022) - Fu, Fangyi; Doroudgar, Shirin
Abstract : Most cellular protein synthesis, including synthesis of membrane-targeted and secreted proteins, which are critical for cellular and organ crosstalk, takes place at the endoplasmic reticulum (ER), placing the ER at the nexus of cellular signaling, growth, metabolism, and stress sensing. Ample evidence has established the dysregulation of protein homeostasis and the ER unfolded protein response (UPR) in cardiovascular disease. However, the mechanisms of stress sensing and signaling in the ER are incompletely defined. Recent studies have defined notable functions for the inositol-requiring kinase 1 (IRE1)/X-box- binding protein-1 (XBP1) branch of the UPR in regulation of cardiac function. This review highlights the mechanisms underlying IRE1 activation and the IRE1 interactome, which reveals unexpected functions for the UPR and summarizes our current understanding of the functions of IRE1 in cardiovascular disease.